Conhecimentos e práticas do uso de plantas medicinais com Abordagem etnobotânica, no município de Morrinhos-Goiás : estudo de caso - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
Beside the knowledge and treatments established by the Scientific Medicine and which are hegemonic in the Public Health System, survive in the memory of people the conceptions, beliefs and customs that compound the Popular Medicine, namelye, the traditional knowledge about herbal treatments, that since the beginning of mankind, passed down from generation to generation through oral and familiar transmission. The association between these two types of knowledge and treatment of diseases, consist today in an interesting aspect of our culture. Considering these aspects, this study aims to reflect about the changes of the popular practice of medicine, taking into consideration the historical aspects that make up these practices. Besides that, it seeks to highlight the importance of traditional knowledge of the population, specifically regarding medicinal plants. In this study, we will launch the look of Cultural History and Oral History about the memories and stories (experience) of rootworker Ivanir Francisca da Silva and Maria de Lurdes Silva, who live in the county of Morrinhos (GO). From their own life stories, we find some of the popular traditions that survived the predominance of scientific knowledge in the medical field, thus, we seek to understand the means of transmission and maintenance of this knowledge, which today receives new looks in different areas of knowledge.
Keywords: Plantas medicinais; Medicina popular; Raizeiras; Medicinal plants; Folk medicine; Rootworker; OUTROS